The Christian Moses : From Philo to the Qur'an - Timbie, Janet; Rousseau, Philip (Book collections on Project MUSE., 2019)
As it developed an increasingly distinctive character of its own during the first six centuries of the common era, Christianity was constantly forced to reassess and adapt its relationship with the Jewish tradition. The process involved a number of preoccupations and challenges: the status of biblical and parabiblical texts (several of them already debatable in Jewish eyes), the nature and purposes of God, patterns of prayer (both personal and liturgical), ritual practices, ethical norms, the acquisition and exercise of religious authority, and the presentation of a religious "face" to the very different culture that surrounded and in many ways dominated both Christians and Jews. The essays in this volume were developed within that broad field of inquiry, and indeed make their contribution to it. For, among the many issues already mentioned, there was also that of persons. What was Christianity to do, not just with Adam or Noah, say, but with Abraham, David and Solomon, the great prophetic figures of Jewish history-and, of course, with Moses? As we move, chapter by chapter, across the early Christian centuries, we see Moses gradually changing in Christian eyes, and at the hands of Christian exegetes and theologians, until he becomes the philosopher par excellence, the forerunner of Plato, the archetype of the lawgiver, the model shepherd of the people of God-yet all on the basis of a scriptural record that Jews would still have been able to recognize